COVID-19 pandemic crisis and food safety: Implications and inactivation strategies. (March 2021) - Han, Sangha; Roy, Pantu Kumar; Hossain, Md Iqbal; Byun, Kye-Hwan; Choi, Changsun; Ha, Sang-Do
Abstract: Background: The COVID-19 pandemic that emerged in 2019 has imposed huge consequences, including economic losses and threats to human health, which are still affecting many aspects throughout the world. Scope and approach: This review provides an overview of SARS-CoV-2 infection, the cause of COVID-19, and explores its impact on the food supply system and food safety. This review examines the potential risk of transmission through food and environmental surfaces before discussing an effective inactivation strategy to control the COVID-19 pandemic in the aspect of food safety. This article also suggests effective food safety management post-COVID-19. Key findings and conclusions: Respiratory viruses including SARS-CoV-2 are responsible for huge impacts on the global economy and human health. Although food and water are not currently considered priority transmission routes of SARS-CoV-2, infection through contaminated food and environmental surfaces where the virus can persist for several days cannot be ignored, particularly when the surrounding environment is unhygienic. This approach could help determine the exact transmission route of SARS-CoV-2 and prepare for the post-COVID-19 era in the food safety sector. Highlights: ● COVID-19 pandemic has brought huge implication in many sectors including food supply and safety. ● There is no evidence that food is a likely transmission route of SARS-CoV-2, however potential risks of infection via food and water cannot be ignored as high persistence of the virus on food and environmental surfaces. ● Effective strategy for inactivating SARS-CoV-2 and monitoring of the virus infection in food and environmental sector are essential in order to control rapid spreading of COVID-19.